Would wax glands help us to understand the relationships among corbiculate bees? - Noll, F. B. [UNESP]; Justino, C. E. L. [UNESP]; Almeida, E. A. B.; Mateus, S.; Billen, J. (Springer, 2021)
Many of the phenotypic manifestations present in social insects are related to the development of exocrine glands, well represented by the nest-building behaviors. Among bees, four tribes compose the corbiculate bees, including both solitary and eusocial species: Apini, Bombini, Euglossini and Meliponini, which use wax as an endogenous product to construct several structures of their nests. Previous works described the presence of wax glands dorsally in meliponine bees, ventrally in Apis, and dorsally and ventrally in Bombus. In euglossine bees, there is some confusion about the presence and location of wax glands. This work, therefore, aims to investigate the position of the wax glands in the four tribes regarding the literature uncertainty. In addition, gathering more information allows a better interpretation of the evolution of this structure and provides more information on the evolution of corbiculate bees. In this work, we collected females from the four tribes of corbiculate bees in the active building area of the nest. Our data showed the presence of wax glands dorsally in Meliponini, ventrally in Apini, and ventrally and dorsally in Bombini; however, no trace of the wax gland was found in Euglossini. Therefore, the absence of wax products in Euglossini suggests that wax glands are an important component of social life and it should be understood as a unique acquisition of the clade formed by the three eusocial corbiculate bee tribes (Bombini, Meliponini and Apini).
Keywords: Anatomy; Apini; Bombini; Euglossini; Meliponini; Sociality